In the presence of TGF-β1, Asperosaponin VI promotes human mesenchymal stem cell differentiation into nucleus pulposus like- cells - Yong-tao Niu (BMC Complementary Medicine and Therapies, 2021)
Abstract Background The regeneration of nucleus pulposus (NP) cells is an effective method to prevent intervertebral disc degeneration (IVDD). In this study, we investigated the role of Asperosaponin VI (ASA VI), isolated from a traditional Chinese medicine (TCM), the root of Dipsacus asper Wall, in promoting human mesenchymal stem cell (HMSC) proliferation and differentiation into NP-like cells and explored the possible mechanism of action. Methods The effects of ASA VI on HMSC viability and proliferation were determined by the XTT method and EDU staining. Then, Real-time qPCR, immunocytochemistry and immunofluorescence assays were used to measure the effect of ASA VI on the expression of extracellular matrix (ECM) components, such as COL2A1, aggrecan, SOX9, KRT19, PAX1, and glycosaminoglycans (GAGs), in NP cells. In addition, Western blot assay was used to measure the expression of p-ERK1/2 and p-smad2/3. Results ASA VI was able to promote the proliferation and differentiation of HMSCs into NP-like cells, and the optimum concentration was 1 mg/L. Western blot assay indicated that the possible mechanism might be related to the activation of p-ERK1 / 2 and p-Smad2 / 3. Conclusions ASA VI can promote the proliferation and differentiation of HMSCs into NP-like cells, which can potentially be used as a treatment for IVDD.